Pulmonary vascular endothelium: the orchestra conductor in respiratory diseases: Highlights from basic research to therapy - Huertas, Alice; Guignabert, Christophe; Bärtsch, Peter (The European respiratory journal, 2018)
The European Respiratory Society (ERS) Research Seminar entitled “Pulmonary vascular endothelium: orchestra conductor in respiratory diseases - highlights from basic research to therapy” brought together international experts in dysfunctional pulmonary endothelium, from basic science to translational medicine, to discuss several important aspects in acute and chronic lung diseases. This review will briefly sum up the different topics of discussion from this meeting which was held in Paris, France on October 27-28, 2016. It is important to consider that this paper does not address all aspects of endothelial dysfunction but focuses on specific themes such as: 1) the complex role of the pulmonary endothelium in orchestrating the host response in both health and disease (acute lung injury, chronic obstructive pulmonary disease, high-altitude pulmonary oedema and pulmonary hypertension); and 2) the potential value of dysfunctional pulmonary endothelium as a target for innovative therapies. - Tweetable abstract ERSpublications - click to tweetThe central role of pulmonary endothelial dysfunction in respiratory diseases http://ow.ly/tVgK30iiZ1S
Gesehen am 04.11.2019